Carbon nanotube anions for the preparation of gold nanoparticle–nanocarbon hybrids. Issue 9 (18th December 2015) - Bayazit, Mustafa K.; Hodge, Stephen A.; Clancy, Adam J.; Menzel, Robert; Chen, Shu; Shaffer, Milo S. P.
Abstract : This methodology highlights the unusual chemistry of negatively charged carbon nanotubes and provides a blueprint for the generation of hybrid nanomaterials. Abstract : Gold nanoparticles (AuNPs) can be evenly deposited on single-walled carbon nanotubes (SWCNTs) via the reduction of the highly stable complex, chloro(triphenylphosphine) gold(i ), with SWCNT anions ('nanotubides'). This methodology highlights the unusual chemistry of nanotubides and provides a blueprint for the generation of many other hybrid nanomaterials.